Odpowiedź:
[tex]\frac{5x-3}{4} + 3 = 2x |*4\\5x - 3+ 12 = 8x \\5x - + 9 = 8x \\5x - 8x = -9\\-3x = -9 |:(-3)\\x = 3[/tex]
[tex]x - \frac{2x+3}{5} = 3 |*5\\5x - 2x + 3 = 15 \\3 x = 15 - 3\\3x = 12 |:3\\x = 4[/tex]
[tex]4 - \frac{x}{4} = 2x - \frac{1}{2} |*4\\16 - x = 8x -2\\- x - 8x = -2 - 16\\- 9x = -18 |:(-9)\\x = 2[/tex]
[tex]\frac{2x}{3} + 4 = \frac{x+2}{3} |*3\\2x + 12 = x+2 \\2x - x = 2 - 12 \\x = - 10[/tex]
[tex]\frac{3x-2}{5} -2 = \frac{x}{5} |*5\\3x - 2 - 10 = x \\3x - 12 = x \\3x - x = 12\\2x = 12 |:2\\x = 6[/tex]